The profile of nursing professionals who get injured with piercing and cutting materials in their job atmosphere - Dias, Fernanda Lima Aragão; Pinheiro, Patrícia Neyva da Costa; Barroso, Maria Grasiela Teixeira (Rev Rene, 2006)
The work accidents are a constant in the nursing professionals’ lives. It is important not to forget that such professionals spend most of their lives hospital of infectious diseases atmosphere and that they are always exposed to all kinds of risks. In this research we aimed at identifying the profile of the professionals who have been injured with piercing and/or cutting materials. To obtain the data we used a descriptive research from the months of January to April 2004, with 99 professionals. We realized then that most of the professionals who have suffered a work accident are female. They are nursing auxiliaries and have been working for about nine to eighteen years and didn’t accomplish the necessary measures after the accident. Nevertheless, we suggest to the institution the implantation and implementation of actions to make the professionals conscious of the need to insert the preventive measures in their daily activities.